Peran Orang Tua terhadap Implementasi Kurikulum Merdeka di SDN Gadang 2 Banjarmasin - A, Nurlaili Fitriyah; Yulianita, Riska; Anastasia, Anastasia; Ni’mah, Wahidatun; Pratiwi, Diani Ayu (MASALIQ, 2025)
This study is motivated by the limited research on parental involvement in the implementation of the Merdeka Curriculum, despite its significant impact on students’ academic achievement and character development, especially in elementary schools with limited resources. The study aims to explore the effects of low parental involvement on student learning and to identify its underlying causes at SDN Gadang 2 Banjarmasin. A qualitative case study approach was employed with 10 purposively selected participants, including parents, teachers, and the vice principal. Data were collected through semi-structured interviews, field observations, and document analysis, and examined using thematic analysis. The findings reveal that low parental involvement is primarily due to economic hardship, limited education, and social norms that perceive schooling as a mere formality. These results highlight the importance of strong collaboration between families and schools. The study concludes that raising parental awareness and reinforcing synergy among schools, families, and communities are essential to support the success of the Merdeka Curriculum. The research contributes theoretically to the literature on family roles in primary education and practically by recommending continuous parenting programs and intensive curriculum outreach by schools.